Perifosine, a Bioavailable Alkylphospholipid Akt Inhibitor, Exhibits Antitumor Activity in Murine Models of Cancer Brain Metastasis Through Favorable Tumor Exposure - Taniguchi, Keisuke; Suzuki, Tomo; Okamura, Tomomi; Kurita, Akinobu; Nohara, Gou; Ishii, Satoru; Kado, Shoichi; Takagi, Akimitsu; Tsugane, Momomi; Shishido, Yoshiyuki (Frontiers in Oncology, 2021)
Metastatic brain tumors are regarded as the most advanced stage of certain types of cancer; however, chemotherapy has played a limited role in the treatment of brain metastases. Here, we established murine models of brain metastasis using cell lines derived from human brain metastatic tumors, and aimed to explore the antitumor efficacy of perifosine, an orally active allosteric Akt inhibitor. We evaluated the effectiveness of perifosine by using it as a single agent in ectopic and orthotopic models created by injecting the DU 145 and NCI-H1915 cell lines into mice. Initially, the injected cells formed distant multifocal lesions in the brains of NCI-H1915 mice, making surgical resection impractical in clinical settings. We determined that perifosine could distribute into the brain and remain localized in that region for a long period. Perifosine significantly prolonged the survival of DU 145 and NCI-H1915 orthotopic brain tumor mice; additionally, complete tumor regression was observed in the NCI-H1915 model. Perifosine also elicited much stronger antitumor responses against subcutaneous NCI-H1915 growth; a similar trend of sensitivity to perifosine was also observed in the orthotopic models. Moreover, the degree of suppression of NCI-H1915 tumor growth was associated with long-term exposure to a high level of perifosine at the tumor site and the resultant blockage of the PI3K/Akt signaling pathway, a decrease in tumor cell proliferation, and increased apoptosis. The results presented here provide a promising approach for the future treatment of patients with metastatic brain cancers and emphasize the importance of enriching a patient population that has a higher probability of responding to perifosine.